Pengaruh Brand Image, dan Sales Promotion Terhadap Keputusan Berbelanja di Matahari Departement Store Pakuwon Mall Solo yang di Mediasi Brand Trust - Lulu Amira Zulfa; Lukman Hakim (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the influence of brand image and sales promotion on consumers’ purchase decisions at Matahari Department Store Pakuwon Mall Solo, with brand trust as a mediating variable. The research employed a quantitative approach using a survey method and purposive sampling technique. Respondents were individuals aged 17 and above, residing in Solo City, and had experience shopping for clothing at the research site. Data were analyzed using structural equation modeling. The results reveal that brand image significantly affects purchase decisions, while sales promotion and brand trust do not have a significant influence. Furthermore, brand image and sales promotion positively influence brand trust. However, brand trust fails to mediate the relationship between both brand image and sales promotion with purchase decisions.